Critical Management Studies Courses: Impact on the Adult Learners' Management Philosophy? - Catherine H. Monaghan (Adult Education Research Conference, 2004)
This paper presents the findings of a study examining the development of the adult learners’ management philosophy in a critical management course. This study found that these courses could impact a learners’ management philosophy in multiple ways within the same course.